2017
DOI: 10.1186/s13023-017-0571-y
|View full text |Cite
|
Sign up to set email alerts
|

The RENAPE observational registry: rationale and framework of the rare peritoneal tumors French patient registry

Abstract: BackgroundRare peritoneal cancers represent complex clinical situations requiring a specific and multidisciplinary management. Because of their rarity, lack of awareness and knowledge often leads to diagnostic delays and misdiagnosis. And patients are not systematically referred to expert centers as they should be. Clinicians and researchers also face unique challenges with these rare cancers, because it is hard to conduct adequately powered, controlled trials in such small patient population. This is how an o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 50 publications
0
22
0
Order By: Relevance
“…Data were collected from the French National Network of Peritoneal Surface Malignancies (RENAPE) database, which includes patients treated for PMP at 20 centres of expertise in peritoneal surface malignancy between 1994 and 2016. All patients with pathologically confirmed PMP treated with CCRS and HIPEC were selected for this study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Data were collected from the French National Network of Peritoneal Surface Malignancies (RENAPE) database, which includes patients treated for PMP at 20 centres of expertise in peritoneal surface malignancy between 1994 and 2016. All patients with pathologically confirmed PMP treated with CCRS and HIPEC were selected for this study.…”
Section: Methodsmentioning
confidence: 99%
“…For each patient, the data were extracted from the RENAPE database, which complies with applicable local regulations and with the ethical principles (Declaration of Helsinki, Fortaleza 2013) relating to data processing, files, and personal freedom and privacy.…”
Section: Methodsmentioning
confidence: 99%
“…A recent publication has already shown that 90 days morbidity is better evaluated with CTCAE v5.0 than with the Clavien Dindo classification in patients who underwent CRS and hyperthermic intraperitoneal chemotherapy [29]. As PIPAC is a drug delivery method, it can be inferred that this classification is also superior to the Clavien Dindo classification [28]. However, the latter will also be present in the CRF for comparative purposes.…”
Section: Discussionmentioning
confidence: 99%
“…The functioning of the registry has been described elsewhere [8]. Briefly, the registry enrolls patients with PM who have undergone palliative or potentially curative surgical treatment for PM.…”
Section: Methodsmentioning
confidence: 99%
“…Surgeons/ centres from neighbouring countries are also enrolled in the registry. The importance of such a registry [7] has been demonstrated by the scientific contributions made by two national registries: the RENAPE [8] and BIG-RENAPE [9] in France and the Netherlands cancer registry [10] in the Netherlands.…”
Section: Introductionmentioning
confidence: 99%